Aggressive hydration with lactated Ringer’s solution versus plasma solution for the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (ALPS study): protocol for a multicentre, double-blind, randomised controlled trial - In Rae Cho; Sang Hyub Lee; Jin Ho Choi; Joo Kyung Park; Gunn Huh; Woo Hyun Paik; Do Hyun Park (BMJ Open)
Introduction Endoscopic retrograde cholangiopancreatography (ERCP) plays an indispensable role in treating pancreato-biliary diseases but carries a risk of post-ERCP pancreatitis (PEP). Despite advances in the prevention strategies, prevention of PEP remains imperfect, necessitating more refined hydration methods. This study investigates the effectiveness of lactated Ringer’s solution versus plasma solution in preventing PEP.Method and analysis This multicentre, double-blind, randomised controlled trial, will be initiated by the investigator-sponsor, and conducted in three tertiary centres in South Korea. The aim of this study is to assess the effectiveness of hydration in preventing PEP in patients with naïve papillae. It will target patients with naïve papillae, focusing on those at medium to high risk of PEP. Patients aged ≤18 years and those with serious comorbidities, acute/chronic pancreatitis and various other medical conditions will be excluded. Eligible participants will be randomly assigned into two arms in equal numbers: (1) PEP prevention using lactated Ringer’s solution and (2) PEP prevention using plasma solution. The primary outcome of this study will be the occurrence of PEP, and secondary outcomes will be additional risk factors and potential adverse events related to ERCP. With a total enrolment of 844 patients, the study will be able to detect significant differences between the intervention arms.Ethics and dissemination Ethical approval is obtained from each institution (Asan Medical Centre, 2023-0382; Seoul National University Hospital, H-2302-05-1404; Samsung Medical Centre, SMC 2023-02-001-009). All participants provided informed consent following clear explanation of the study procedures. The results of the study will be disseminated in peer-reviewed journals and research conferences.Trial registration number NCT05832047.Protocol version Ver 4.1 (2023).